2021
DOI: 10.1007/s10856-021-06580-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lactide vs glycolide composition of poly (lactic-co-glycolic acid) polymers on encapsulation of hydrophobic molecules: molecular dynamics and formulation studies

Abstract: The work demonstrates the preparation of PLGA (PLGA 50:50, PLGA 75:25) nanoparticles, to encapsulate a hydrophobic molecule (coumarin-6), using the microreactor-based continuous process. The formulations were characterized using dynamic light scattering and transmission electron microscopy to determine their size, homogeneity, zeta potential, and surface morphology. The resulting nanoparticles were safe to the CHO cells (≈80% cell survival), at the concentration of ≤600 µg/mL and were successfully taken up by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…To compare the drug release profiles and kinetics of the PLGA nanocapsules with and without metal deposition, release studies were performed by detecting the druglike fluorophore molecule coumarin-6. Interestingly, no significant differences were observed in the release profile and kinetics between the metal-coated and uncoated nanocapsules (∼41% over 168 h), being similar to other reports on the release kinetics of coumarin-6 from PLGA NPs (33–45% over 168 h). A similar release pattern of the paclitaxel drug was also observed in our previous work for Fe-coated and uncoated polymer nanoparticles . These results indicate that neither the metal layer nor the deposition process reduced the percentage and extension of the drug release (Figure E), thereby preserving the water hydrolysis of the polymer chains that triggers the polymer degradation .…”
Section: Resultssupporting
confidence: 89%
“…To compare the drug release profiles and kinetics of the PLGA nanocapsules with and without metal deposition, release studies were performed by detecting the druglike fluorophore molecule coumarin-6. Interestingly, no significant differences were observed in the release profile and kinetics between the metal-coated and uncoated nanocapsules (∼41% over 168 h), being similar to other reports on the release kinetics of coumarin-6 from PLGA NPs (33–45% over 168 h). A similar release pattern of the paclitaxel drug was also observed in our previous work for Fe-coated and uncoated polymer nanoparticles . These results indicate that neither the metal layer nor the deposition process reduced the percentage and extension of the drug release (Figure E), thereby preserving the water hydrolysis of the polymer chains that triggers the polymer degradation .…”
Section: Resultssupporting
confidence: 89%
“…Evidence suggests that interaction of PLGA polymers with biologically active molecules depends on their surface properties. PLGA 50:50, with its balanced ratio of lactic to glycolic acids presents a more hydrophilic surface 54 , 55 than the more hydrophobic PLGA 75:25 resomer. Tau protein, being predominantly hydrophilic and enriched with charged amino acids, it is likely to interact favorably with hydrophilic surfaces of PLGA 50:50 which could sterically hinder self-association of tau molecules leading to reduction in its aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that the growth of individual Ag or Au nanodots can be controlled by varying the beam intensity, the concentration of the metal salt, and the flow rate within the microreactor. Dobhal et al 239 from the Institute of Chemical Technology in India prepared poly (lactic-co-glycolic acid) (PLGA)encapsulated coumarin-6 nanoparticles on a microreactor continuous platform. Multiple test results show that the nanoparticles are safe to CHO cells (E80% cell viability) at a concentration of r600 mg mL À1 and can be successfully absorbed by cells.…”
Section: Synthesis Of Composite Micro/nanomaterialsmentioning
confidence: 99%
“…Dobhal et al 239 from the Institute of Chemical Technology in India prepared poly (lactic- co -glycolic acid) (PLGA)-encapsulated coumarin-6 nanoparticles on a microreactor continuous platform. Multiple test results show that the nanoparticles are safe to CHO cells (≈80% cell viability) at a concentration of ≤600 μg mL −1 and can be successfully absorbed by cells.…”
Section: Synthesis Of Micro/nanomaterials By Microreactorsmentioning
confidence: 99%